Slavery's Bestiary: Joel Chandler Harris's Uncle Remus Tales. - Peterson, Christopher (Paragraph, 2011)
The critical reception of Joel Chandler Harris's Uncle Remus Tales has often interpreted these animal fables as allegories of American slavery. Such an approach, however, risks what Steve Baker calls the ''denial of the animal'', which displaces animal signifiers onto human signifieds. Through readings of ''The Wonderful Tar-Baby Story'' and ''How the Birds Talk'', I ask what it might mean to take seriously the numerous historical, political and philosophical questions posed by the animal ''form'' that these characters assume, including Heidegger's ontological differentiation between thing, animal and human, and Derrida's displacement of the conventional Cartesian distinction between animal reaction and human response. I argue that the racist equation of blacks with mimicry relies precisely on this dubious opposition. Remus's stories thus challenge our understandings of both race and language by showing how repetition and mimicry condition every ''human'' response.